PENGEMBANGAN MODUL IPA MATERI HUBUNGAN MAKHLUK HIDUP DAN LINGKUNGANNYA BERBASIS PENDEKATAN KONTEKSTUAL - Sari Damara Gita; Muhsinah Annisa; Wilda Indra Nanna (Faculty of Teaching and Education, University of Wiraraja, 2018)
This study aimed to produce teaching materials in the form of IPA Modules of living creatures and the environment based on a quality contextual approach in terms of expert validation and testing to students. This development research uses the ADDIE model development procedure (analysis, design, development, implementation, evaluation). The subjects of this study are students of grade IV-B SD Negeri 033 Tarakan with a total of 24 people. Criteria for quality of IPA module material of living creature relationship and environment, viewed material validation result 98% (very valid), design validation 87.5% (very valid), validation of language 97% (very valid), 100% validation validation (very valid) and validation practitioner 88% (very valid), so the average validation result gets a percentage of 94% (very valid). Based on the questionnaire, the students' responses were 93% (very good) Based on what has been explained that the IPA module based on the contextual approach that has been developed is qualified.